ANALISIS HUKUM MEMBACA SURAH AL-FATIHAH DALAM SHALAT SENDIRIAN; STUDI KOMPARATIF ANTARA PENDAPAT IMAM HANAFI DAN IMAM SYAFI’I - Nasution, Buyung Saroha (IAIN Padangsidimpuan, 2021)
This journal is entitled the legal analysis of reading Surah al-Fatihah in prayer alone. Comparative Studies between the Opinions of Imam Hanafi and Imam Shafi'i. Junal is a comparative study to find out the differences of opinion between Imam Hanafi and Shafi'i on the law of reading Surah al-Fatihah in prayer alone. In carrying out the study, the author collects the arguments used by Imam Hanafi and Imam Shafi'i in determining the law of reading Surah al-Fatihah in prayer alone, then the author analyzes the arguments of both of them in terms of the science of ulumul hadith on the transmission of the hadith arguments which are the differences in their understanding, and analyzing the science of usul fiqh with the al-jam'u wa at-taufiq method in ta'arud al-adilla.